E-journals, researchers and the new librarians - David NICHOLAS, Ian ROWLANDS and Peter WILLIAMS (Learned Publishing, 2415:15-27, 2011)
This paper provides the results of a two-year investigation into the use of e-journals bythe UK research community. Log analysis, questionnaires, interviews, and observation were used to collect the information. The results are presented in a FAQ format to make the key findings accessible. The main findings are that journals have become central to most disciplines, and that the e-form has become the prime means of access. Theresults for history suggest that the old scholarly communication mantras (scientists primarily communicate through articles, historians through monographs) are rapidly breaking down. Indeed, all researchers seem addicted to journal content. Research without this resource now seems unthinkable; journals are a researcher's lifeblood.Gateway services, hugely popular in science, are re-intermediating the broken chain between publisher and reader; they are the new librarians.